Second-messenger regulation of receptor association with clathrin-coated pits: a novel and selective mechanism in the control of CD4 endocytosis. - Foti, M (1997)
CD4, a member of the immunoglobulin superfamily, is not only expressed in T4 helper lymphocytes but also in myeloid cells. Receptor-mediated endocytosis plays a crucial role in the regulation of surface expression of adhesion molecules such as CD4. In T lymphocytes p56lck, a CD4-associated tyrosine kinase, prevents CD4 internalization, but in myeloid cells p56lck is not expressed and CD4 is constitutively internalized. In this study, we have investigated the role of cyclic AMP (cAMP) in the regulation of CD4 endocytosis in the myeloid cell line HL-60. Elevations of cellular cAMP were elicited by 1) cholera toxin, 2) pertussis toxin, 3) forskolin and IBMX, 4) NaF, or 5) the physiological receptor agonist prostaglandin E1. All five interventions led to an inhibition of CD4 internalization. Increased cAMP levels did not inhibit endocytosis per se, because internalization of insulin receptors and transferrin receptors and fluid phase endocytosis were either unchanged or slightly enhanced. The mechanism of cAMP inhibition was further analyzed at the ultrastructural level. CD4 internalization, followed either by quantitative electron microscopy autoradiography or by immunogold labeling, showed a rapid and temperature-dependent association of CD4 with clathrin-coated pits in control cells. This association was markedly inhibited in cells with elevated cAMP levels. Thus these findings suggest a second-messenger regulation of CD4 internalization through an inhibition of CD4 association with clathrin-coated pits in p56lck-negative cells.